TAKDIR DAN KEHENDAK MANUSIA DALAM PEMIKIRAN IBNU SINA DAN ARTHUR SCHOPENHAUER : STUDY LITERATUR FILSAFAT DETERMINISME DAN KEBEBASAN - Adnan Risqita Wijaya (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2025)
The struggle of thought about destiny and human will is a central and classic theme in philosophy, especially in the debate between the philosophy of determinism and the philosophy of freedom. In this article, we discuss two great figures, namely Ibn Sina, a Muslim philosopher who put forward his ideas regarding human will as a part that is not far from the active reason that is directed rationally, and Arthur Schopenhauer, a German philosopher who put forward his ideas regarding will as an irrational drive that underlies all human actions. The research in this article uses literature study to explore the theory of how each of these figures formulates the concept of destiny and will. The formulation of the problem in this article is (1) what is the concept of destiny and human will according to Ibn Sina?, (2) what is the concept of human will according to Arthur Schopenhauer in the philosophy of determinism and freedom?, (3) what are the differences and similarities between the thoughts of Ibn Sina and Arthur Schopenhauer about destiny and human will.? The results of the discussion of this article show that although the two figures come from different backgrounds, both figures agree to reject absolute human freedom. Both figures also acknowledge the will that exists in humans, but it should be underlined that the will remains within certain limits according to Ibn Sina, or an unconscious and blind will according to Arthur Schopenhauer. The conclusion of this article is that the views of both complement each other in describing the connection between destiny and will, and in this case show a complex relationship between determinism and freedom in will.